White light-excited organic room-temperature phosphorescence for improved in vivo bioimaging - Lutong Zhang; Jisen Li; Yifan Zhang; Wenbo Dai; Yufan Zhang; Xue Gao; Miaochang Liu; Huayue Wu; Xiaobo Huang; Yunxiang Lei; Dan Ding (Nature Communications)
Abstract Organic phosphorescence materials offer significant advantages for bioimaging applications. However, most of these materials are excited exclusively by ultraviolet (UV) light, which poses risks to living organisms. Herein, six donor–acceptor-type compounds incorporating triazine groups are designed as guests within doped systems. White-light excitable phosphorescent guests enable doped materials to show efficient afterglow under white-light excitation. By leveraging the ability of white-light to penetrate biological tissues, a bioimaging mode in which the materials are first concentrated within the organism and then excited was developed, yielding superior imaging effects compared with the traditional method in which materials are first excited and then concentrated. Furthermore, these materials are applied in imaging diagnosis of atherosclerosis plaques (male Apoe− / − mice) and intestinal diseases (female BALB/c-nude mice), as well as in navigation for in situ liver tumor surgery (female BALB/c-nude mice), achieving excellent imaging outcomes. This work addresses the limitations of phosphorescent materials that rely on UV-light, significantly enhancing their potential for practical applications in clinical imaging.